Effects of Artemisia argyi Powder on Egg Quality, Antioxidant Capacity, and Intestinal Development of Roman Laying Hens - Chen, Jiayi; Chen, Fengming; Peng, Simin; Ou, Yangjiang; He, Binsheng; Li, Yinghui; Lin, Qian (Frontiers in Physiology, 2022)
This study was conducted to evaluate the effect of dietary supplementation with Artemisia argyi (A. argyi) on egg quality, serum biochemical, antioxidant capacity and intestinal development in Roman laying hens. A total of 432 (34-week-old) Roman hens were randomly divided into control group and three experimental groups. The control group was fed basal diet, and the experimental group was fed basal diet with 1%, 2% and 3% A. argyi powder, respectively. The results showed that dietary supplementation of 2% A. argyi to the diet increased egg weight and egg white weight, and the daturic acid (C17:0), stearic acid (C18:0), eicosadienoic acid (C20:2), docosahexaenoic acid (C22:6n-3), α-linolenic acid (C18:3n-3), linoleic acid (C18:2n-6c) and polyunsaturated fatty acid (PUFA) in egg yolk. Meanwhile, the addition of 1∼3% A. argyi decreased serum urea. Moreover, dietary supplementation of 1% A. argyi promoted the antioxidative capacity of the hens by increasing hepatic T-SOD and CAT activities, as well as GSH-Px content. However, the addition of 3% A. argyi to the diet significantly increased the content of MDA in serum and liver and destroyed the intestinal morphology by increasing duodenal crypt depth. In conclusion, the addition level of A. argyi promoting egg quality and antioxidant capacity was at 2% and 1%, respectively.